Pengenalan Manipulasi Data dengan Menggunakan Bahasa Pemrograman R pada Guru SMK Sumber Ilmu Tulangan - Fitriani, Fenny; Indrasetianingsih, Artanti; Pramesty, Maria Hernita Elvine; Amin, Mochammad Iqbal Nasrulloh Al (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Ivet, 2023)
Data processing is one of the basics that must be mastered by researchers and people who work with data. One of the people who work with data is a teacher. The data owned by the teacher can be utilized by a teacher in carrying out the classroom action research process. However, the contents of the data that are owned may not necessarily be directly processed. So, it is necessary to have treatment carried out on data such as data manipulation. In the data manipulation process this can be done with the help of software R. Based on this, dedication is carried out in the form of an introduction to data manipulation given to teachers at SMK Sumber Ilmu Reinforcement by using software R. Activities After the activities are carried out, the teacher can better understand how the process correct data manipulation with the help of R software